2013
DOI: 10.1007/s00221-013-3578-1
|View full text |Cite
|
Sign up to set email alerts
|

Is a neutral expression also a neutral stimulus? A study with functional magnetic resonance

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in: El acceso a la versión del editor puede requerir la suscripción del recurso Access to the published version may require subscription AbstractAlthough neutral faces do not initially convey an explicit emotional message, it has been found that individuals tend to assign them an affective content. Moreover, previous research has shown that affective judgments are mediated by the task they have to pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 64 publications
3
16
0
Order By: Relevance
“…The right middle temporal gyrus plays an important role in facial recognition (Carvajal et al 2013), and is activated by both neutral and angry facial expressions (Fusar-Poli et al 2009;Dickie et al 2014), consistent with the view that healthy participants respond simi-larly to both neutral and angry faces at both a behav-ioural and neural level (Lee et al 2008;Ille et al 2011). Nevertheless, participants may interpret neutral faces differently, not only due to the fact that no overt anger is being displayed, but also due to the presenta-tion context -for example, neutral faces are sometimes interpreted more positively if immediately following negative faces and more negatively if following happy faces (Lee et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The right middle temporal gyrus plays an important role in facial recognition (Carvajal et al 2013), and is activated by both neutral and angry facial expressions (Fusar-Poli et al 2009;Dickie et al 2014), consistent with the view that healthy participants respond simi-larly to both neutral and angry faces at both a behav-ioural and neural level (Lee et al 2008;Ille et al 2011). Nevertheless, participants may interpret neutral faces differently, not only due to the fact that no overt anger is being displayed, but also due to the presenta-tion context -for example, neutral faces are sometimes interpreted more positively if immediately following negative faces and more negatively if following happy faces (Lee et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The right fusiform is well known to have a key role in facial recognition (McCarthy et al, 1997; Allison, Puce, Spencer, & McCarthy, ; Puce, Allison, Asgari, Gore, & McCarthy, ). The lingual gyrus has also been reported to be more active when participants viewed emotional compared to neutral images (Kehoe, Toomey, Balsters, & Bokde, ), although neutral faces are not in fact neutral and are not a good baseline (Kouptsova, Leung, & Taylor, ; Carvajal et al, ). Our results confirm the early effects of implicitly presented emotional stimuli on neural processing in the ventral visual stream.…”
Section: Discussionmentioning
confidence: 99%
“…The orbitofrontal areas are well known to be crucial for many emotional functions, including appraisal and assigning a motivational value to stimuli for both positive and negative emotions. These areas are also possibly linked with the experience of affective value of both concrete and abstract stimuli (O’Doherty et al 2003 ; Rolls and Grabenhorst 2008 ; Carvajal et al 2013 ). It has also been shown that distinct OFC regions can be associated with either positive or negative emotions (Kringelbach 2005 ).…”
Section: Discussionmentioning
confidence: 99%